A comparative experimental analysis of combustion in a diesel engine fuelled with biodiesel and diesel fuel. Issue 1 (2nd January 2017) - Senthil, R.; Silambarasan, R.; Pranesh, G.
ABSTRACT: The aim of this present study is to analyse the combustion characteristics of a single cylinder, direct injection, compression ignition engine fuelled with Annona methyl ester (AME) and diesel blends. AME is blended with diesel at various blending ratios such as 20, 40, 60, 80 and neat diesel. Engine combustion parameters such as heat release rate (HRR), peak pressure, rate of pressure rise, combustion duration and ignition delay were examined. The ignition delay, maximum HRR and combustion duration were lower with AME–diesel blends, when compared to that of neat diesel fuel. AME is indeed a suitable source for biodiesel with appropriate environmental benefits.